GENERAL OVERVIEW OF HEALTH LAW IN INDONESIA - Dwi Faradina; Tri Faranita; Henry Aspan (CV. RADJA PUBLIKA, 2024)
Initially, health development relied on efforts to treat disease and restore health, shifting to implementing comprehensive health efforts with an emphasis on efforts to prevent disease and improve health. Adequate health legal instruments are intended to provide legal certainty and comprehensive protection for both providers of health efforts and communities receiving health services. The legal basis for health is regulated in Law Number 36 of 2009 concerning health. Health Law is all legal provisions that relate directly to health maintenance/services. This concerns the rights and obligations of receiving health services (both individuals and levels of society) as well as the implementation of health services in all its aspects, organization, facilities, medical service standards and so on. A Health Worker is any person who dedicates themselves to the health sector and has knowledge and/or skills through education in the health sector, which for certain types requires authority to carry out health efforts. As legal subjects, actors in the health sector such as doctors, dentists, hospital directors, heads of health services, heads of divisions, heads of community health centers always carry out legal actions. Legal actions taken if they conflict with applicable regulations will result in legal sanctions.